2007
DOI: 10.1111/j.1432-2277.2006.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

PPAR? agonists improve renal preservation in kidneys subjected to chronic in vitro perfusion: interaction with mannitol

Abstract: Summary We developed methods for prolonged (12 h), sterile, normothermic perfusion of rat kidneys and screened compounds for renal preservation including: mitochondrial transition pore inhibitor (decylubiquinone); caspase inhibitor (Z‐VAD); peroxisome proliferator‐activated receptor‐alpha (PPARα) agonists (gemfibrozil, WY‐14643); antioxidants (trolox, luteolin, quercetin); growth factors (HGF, PDGF, EGF, IGF‐1, VEGF, transferrin); calpain inhibitor (Z‐Val‐Phe‐CHO); calmodulin inhibitor (W7); KATP opener (minox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…These negative effects might contribute to the recently reported potential adverse cardiovascular effects of rosiglitazone in type 2 diabetes (54). Similarly, some clinical activities of fibrates, such as preservation of renal function and amelioration of endothelial dysfunction (55,56), might be partially explained by PPAR␣-induced angiogenesis and VEGF production. In conclusion, we used selective synthetic agonists of PPAR␣ and PPAR␥ and demonstrated that the stimulation of these nuclear receptors results in the activation of a strong neoangiogenic process in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…These negative effects might contribute to the recently reported potential adverse cardiovascular effects of rosiglitazone in type 2 diabetes (54). Similarly, some clinical activities of fibrates, such as preservation of renal function and amelioration of endothelial dysfunction (55,56), might be partially explained by PPAR␣-induced angiogenesis and VEGF production. In conclusion, we used selective synthetic agonists of PPAR␣ and PPAR␥ and demonstrated that the stimulation of these nuclear receptors results in the activation of a strong neoangiogenic process in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NF-κB and COX-2 enzymic activity is often correlated with the disease severity of RA. Fibrate groups of drugs inhibit the expression of COX-2 and prostaglandin synthesis by interfering NF-κB activation [54]. Furthermore, gemfibrozil, known to switch Th1 to Th2 (14), may also lower the burden of Th1 cytokines in RA.…”
Section: Anti-inflammatory Activity Of Gemfibrozilmentioning
confidence: 99%
“…At extracellular level, PPAR alpha modulate lipid metabolism be increasing lipolysis of triglycerides (51,205), an event that would eventually lead to the formation of HDL like apolipoproteins A-I and A-II (51,56,57). Besides its effects on lipid metabolism, agonists of PPAR alpha are known to suppress inflammation (58)(59)(60)(61)(62), modulate the immune response (37,38), improve glucose metabolism (62, 152, 206), mitigate apoptosis/necrosis and relax vascular tissue (143)(144)(145)(146)(147)(148)(149)(150)(151)(152)(153), ameliorate nicotine-induced seizures (207)(208)(209)(210)(211) and neuroprotective in Parkinson's disease (212). Similarly, the PPAR alpha agonist, fenofibrate is cardioprotective and has been shown to inhibit left-ventricular hypertrophy, attenuate abnormalities in left-ventricular relaxation and improve systolic dysfunction in Dahl salt-sensitive hypertensive rats (213).…”
Section: Peroxisome Proliferator-activated Receptor Alpha (Ppar Alpha)mentioning
confidence: 99%